2015
DOI: 10.1287/ijoc.2015.0658
|View full text |Cite
|
Sign up to set email alerts
|

A Progressive Hedging Approach for Surgery Planning Under Uncertainty

Abstract: We propose a multistage stochastic mixed-integer programming formulation for the assignment of surgeries to operating rooms over a finite planning horizon. We consider the demand for and the duration of surgery to be random variables. The objective is to minimize three competing criteria: expected cost of surgery cancellations, patient waiting time, and operating room overtime. We discuss properties of the model and an implementation of the progressive hedging algorithm to find near-optimal surgery schedules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Mohiuddin et al [41] identify and review 19 studies related to simulation modelling for emergency departments in the UK. Another comprehensive review of simulation modelling studies in emergency departments for normal and disaster conditions can be found in Gul et al [27]. Among 106 reviewed papers, only few studies consider an optimization approach [1,18,22,51,59].…”
Section: Accident and Emergency Modellingmentioning
confidence: 99%
“…Mohiuddin et al [41] identify and review 19 studies related to simulation modelling for emergency departments in the UK. Another comprehensive review of simulation modelling studies in emergency departments for normal and disaster conditions can be found in Gul et al [27]. Among 106 reviewed papers, only few studies consider an optimization approach [1,18,22,51,59].…”
Section: Accident and Emergency Modellingmentioning
confidence: 99%
“…The steel-maker requires the maximum productivity with the preservation of quality, and thus the relevant parameters of the casting process need to be determined. In terms of the above defined quantities and derived relationships, the deterministic model aims to maximize v z subject to (8), (9), (10), (11), (12), (13).…”
Section: Numerical Continuous Casting Model and Its Deterministic Formentioning
confidence: 99%
“…The vector function g of inequality constraints includes inequality conditions (e. g. Eqs. (12), (13), (17)) while the vector function h of equality constraints incorporates the heat transfer model (Eqs. (8) and 9) and other equality conditions (e. g. Eqs.…”
Section: Progressive Hedging Algorithmmentioning
confidence: 99%
See 2 more Smart Citations